Monitoring Kebocoran Pada Pipa Menggunakan SMS Gateway - Hidra Amnur -; Defni - -; Fatma Adilla - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2015)
Monitoring is the most important thing in a system. Particularly large systems such as the installation of water pipes. Water pipes are installed in various places will be very troublesome to monitor the leak. With the SMS Gateway System, the real data of the sensor water pipes will be displayed and can be accessed on a website. SMS Gateway is an SMS -based system that can be developed in various fields by utilizing the PHP programming language. Through the development of information technology, creates a system that is interconnected to obtain information in real and fast